1978
DOI: 10.1128/jb.136.2.538-547.1978
|View full text |Cite
|
Sign up to set email alerts
|

Repair of cross-linked DNA and survival of Escherichia coli treated with psoralen and light: effects of mutations influencing genetic recombination and DNA metabolism

Abstract: Repair of cross-linked DNA was studied in Escherichia coli strains carrying mutations affecting DNA metabolism. In wild-type cells, DNA strands cut during cross-link removal were rejoined during a subsequent incubation into high-molecular-weight molecules. This rejoining was dependent on gene products involved in genetic recombination. A close correlation was found relating recombination proficiency, the rate of strand rejoining, and formation of viable progeny after DNA cross-linking by treatment with psorale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

1983
1983
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(23 citation statements)
references
References 46 publications
0
23
0
Order By: Relevance
“…, 1976;Poll et al, 1984;Zolan et al, 1982b;Sancar et al, 1986) indicates that an effective repair system for crosslinks must exist. While a number of possible mechanisms have been proposed, the actual mechanism has not been elucidated (Sinden and Cole, 1978;Saffran and Cantor, 1984;Cole, 1973). Of course prokaryotic and eukaryotic systems may utilise different mechanisms for dealing with crosslinks and other bifilar damage in their DNA Each of the furocoumarins produces a slightly different spectrum of photoproducts.…”
Section: Introductionmentioning
confidence: 99%
“…, 1976;Poll et al, 1984;Zolan et al, 1982b;Sancar et al, 1986) indicates that an effective repair system for crosslinks must exist. While a number of possible mechanisms have been proposed, the actual mechanism has not been elucidated (Sinden and Cole, 1978;Saffran and Cantor, 1984;Cole, 1973). Of course prokaryotic and eukaryotic systems may utilise different mechanisms for dealing with crosslinks and other bifilar damage in their DNA Each of the furocoumarins produces a slightly different spectrum of photoproducts.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, E. coli exposed to MMC needs recombination to repair damage done by MMC. It has been reported that in contrast to eukaryotes, E. coli lacks a mechanism to inhibit chromosomal replication when its DNA is damaged (Sinden and Cole 1978;Kuzminov 1999). In addition, DNA replication in E. coli is often the limiting step in their cell cycle (Bremer and Dennis 1996) while eukaryotes can easily cope with a replication delay, as their S phase is only a fraction of their overall cell cycle (Bremer and Dennis 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Because our screening involved enhanced cell killing on mitomycin‐containing plates, the question arises whether a decreased mutagenic bypass could also contribute to host mitomycin sensitivity. Mitomycin C is known to induce mostly interstrand cross‐links that are primarily repaired by recombination (Iyer and Szybalski, 1963; Sinden and Cole, 1978). Accordingly, bacteria expressing no (or inactive) UmuD′C complex have a wild‐type mitomycin sensitivity (Attfield and Pinney, 1984; unpublished data).…”
Section: Discussionmentioning
confidence: 99%